2018
DOI: 10.1371/journal.pone.0191013
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral quantitative computed tomography detects differences at the radius in prepubertal children with cystic fibrosis compared to healthy controls

Abstract: IntroductionIn 2015, 11.9% of people with cystic fibrosis (CF) in the United States had osteopenia, 5.1% osteoporosis, and 0.3% experienced a fracture. Screening for CF-related bone disease starts in childhood, and dual energy x-ray absorptiometry (DXA) is the recommended method. It is unknown whether peripheral quantitative computed tomography (pQCT) can detect deficits earlier than DXA. This study compared pQCT and DXA scans in a group of pre-pubertal children with CF and healthy controls.MethodsThis was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Our findings of pQCT deficits are consistent O’Brien et al and Kelly et al However, in contrast to the present study, O’Brien et al examined the radius, which is a skeletal site exposed to limited weight-bearing loads, and the current study of tibia pQCT utilized more robust reference data [24] , [25] . A cross sectional study using HR-pQCT in adults with CF demonstrated inferior bone microarchitecture that was worse than expected for the lower BMI [9] .…”
Section: Discussionsupporting
confidence: 88%
“…Our findings of pQCT deficits are consistent O’Brien et al and Kelly et al However, in contrast to the present study, O’Brien et al examined the radius, which is a skeletal site exposed to limited weight-bearing loads, and the current study of tibia pQCT utilized more robust reference data [24] , [25] . A cross sectional study using HR-pQCT in adults with CF demonstrated inferior bone microarchitecture that was worse than expected for the lower BMI [9] .…”
Section: Discussionsupporting
confidence: 88%
“…In 2015, 11.9% of CF patients in the United States had osteopenia, 5.1% osteoporosis, and 0.3% experienced a fracture 2,3 . Osteoporosis‐related fractures, especially rib or vertebral fractures, may result in kyphosis, pain while breathing, reduced airway clearance, and impaired physical activity levels, which may further reduce bone acquisition 1,4 …”
Section: Introductionmentioning
confidence: 99%
“…1 In 2015, 11.9% of CF patients in the United States had osteopenia, 5.1% osteoporosis, and 0.3% experienced a fracture. 2,3 Osteoporosis-related fractures, especially rib or vertebral fractures, may result in kyphosis, pain while breathing, reduced airway clearance, and impaired physical activity levels, which may further reduce bone acquisition. 1,4 The European Cystic Fibrosis Bone Mineralization Guidelines recommend dual energy X-ray absorptiometry (DEXA) to assess BMD in all patients from the age of 8 years; measurement should be repeated every one to 5 years, depending on the age of the patient, value of the previous scan, and presence of risk factors (such as physical inactivity and steroid therapy).…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters measured are bone mineral content, bone area and other derived geometric measurements (cross-sectional area, periosteal and endosteal circumferences, cross-sectional moment of inertia) [10]. pQCT has been J o u r n a l P r e -p r o o f used to study the effects of chronic illness on bone density and dimensions in children with a variety of underlying diseases, such as chronic kidney disease [11,12], cystic fibrosis [13], inflammatory bowel disease [14,15], arthritides [16], acute lymphoblastic leukaemia survivors [17], diabetes [18], nephrotic syndrome [19,20], anorexia nervosa [21,22] and Duchenne muscular dystrophy [23].…”
Section: Peripheral Quantitative Computed Tomography (Pqct)mentioning
confidence: 99%